Basketball Skill Achievements: Comparison between Technical Approach and Tactical Approach based on Physical Fitness Level - Nur, Lutfi; Malik, Arief Abdul (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
Learning approaches, such as tactical approach and technical approach, have been widely discussed for promoting physical activity in physical education learning. The application of a suitable learning approach becomes an important issue related to different fitness level of individual. The purpose of this study was to investigate the results of basketball skill learning by applying the learning approaches based on the physical fitness level of adolescent students. A 2 x 2 factorial design (ANOVA) was applied in this study. Forty junior high school male students were involved in this study. They were divided into 4 groups, including 2 high physical fitness groups and 2 low physical fitness groups by applying the tactical approach and technical approach. This study used the Indonesian Physical Fitness Test (TKJI) instrument for the junior high school level and basketball skill test instruments, including passing, shooting, and dribbling tests. The results showed that, overall, students who received the tactical approach were better than students who received the technical approach. In the high physical fitness student group, the tactical learning approach showed a significant impact compared to the technical approach. However, in the students with low physical fitness group, the technical approach had a better effect on the students' basketball skills. It concludes that the two learning approaches are proven to be able to improve the outcomes of basketball skill learning. For that reason, it is recommended to teach basketball skills using a tactical approach to students with good physical fitness. However, if students have low physical fitness, it is suggested that technical learning approaches is given.